PNG provincial hospital boards' compliance with statutory financial reporting obligations - Shardlow, M.; Brown, Alistair (School of Business Law, Curtin Business School, Curtin University of Technology, 2012)
This article employs textual analysis to examine the financial statement reporting by provincial hospital boards in Papua New Guinea (‘PNG’) as they attempt to comply with mandatory financial statement reporting. Hospital boards in PNG are established under the Public Hospital Act 1994 (PNG), which requires the boards to satisfy the accounting, financial management and reporting requirements indicated under the Public Finances (Management) Act 1995 (PNG). The existing literature on hospital board reporting compliance has previously focused on developed countries with sound governance systems and developed infrastructures. In contrast, this paper provides an examination of hospital boards that operate in troublesome governance systems. This information could be of assistance to public entity stakeholders (for example, tax payers, donors and provincial and national governments) in future decision-making. Knowing the extent of reporting compliance allows stakeholders to assess both the performance and accountability of these health organisations.